Roteamento geográfico para redes de sensores e atuadores sem fio em redes urbanas de comunicação - Denardin, Gustavo Weber (2012)
Smart grids and smart utility networks are the next-generation utility networks that intend to provide efficient control and management of utilities such as electricity, natural gas, water and sewage. Communication technology is the essential element for enabling formation of networks where control messages and metering data can be exchanged. In this work it is shown that wireless sensor and actuator networks are suitable candidates to implement this intelligent networks. The main routing algorithms for this category of wireless network are investigated in order to verify its performance when applied to the characteristics of smart utility networks, which are mainly related for large scale networks formed by hundreds to thousands of devices. It is shown that geographic routing is one of the most suitable routing strategies for large scale wireless networks, due to its low overhead and high scalability features. Usually, a geographic routing scheme combines a geographic greedy forwarding with a recovery mechanism to solve the local minima problem. Solutions proposed in the literature commonly combine greedy forwarding with the well known face routing for achieving this goal. However, the average path length in number of hops produced by face routing could be much worse than the optimal topological path in most realistic scenarios. In this work, it is proposed a new intermediate procedure between the geographic greedy mode and the recovery mode in order to improve routing efficiency in number of hops, without network overhead. It exploits the optimal topological route to base stations, obtained by beacon messages, as a resource to find better routes than the ones created by face routing. It is shown by simulations that the proposed hybrid approach leads to a significant improvement of routing performance when applied to combined greedy-face routing algorithms. Furthermore, experimental results obtained through testbeds shown that the proposed maintenance procedures are capable of avoid uctuations in the network infrastructure, providing robust routes for packet forwarding in large scale networks.